Applied Mass Communication Theory : a guide for media practitioners - Rosenberry, Jack; Vicker, Lauren A., 1953- (New York : Routledge, 2022)
"Applied Mass Communication Theory: A Guide for Media Practitioners (Third Edition) connects mass media theory to the contemporary work of media professionals. The text presents vital chronological information on the progression of theory in mass communication, including a model that integrates mass communication theories and shows how they relate to one another. It explores and explains theories from the effects tradition and interpretive tradition from the perspective that using a theoretical framework to understand what happens in the media is essential to understanding how to craft a message. The theory discussion is accompanied by a review of quantitative and qualitative research methods. New for the third edition are expansions of the chapters on interpretive theories, qualitative methods, and media business in the Internet age. A new appendix describes the process of creating an undergraduate research project"--
Revised edition of the authors' Applied mass communication theory, 2017.
Includes bibliographical references and index.
Keywords: Mass media -- Research; Mass media -- Philosophy